Brief repeated virtual nature contact for three weeks boosts university students' nature connectedness and psychological and physiological health during the COVID-19 pandemic: A pilot study - Lau, Sam S. S.; Leung, Sharron S. K.; Wong, Jonathan W. C.; Lee, Terence C. P.; Cartwright, Stephen R.; Wong, Janet T. C.; Man, Jackie; Cheung, Ethan; Choi, Regene P. W. (Frontiers in Public Health, 2023)
The COVID-19 pandemic and its associated uncertainties and restrictions have adverse impacts on university students’ mental well-being. Evidence shows that virtual nature contact has mental health benefits. However, little is known about the potential beneficial health impacts of virtual nature contact during times of social distancing, when access to the natural environment is restricted. This pilot study aimed to examine the effectiveness of a three-week virtual nature contact in improving nature connectedness and reducing psychophysiological stress. A sample of 56 university students in Hong Kong was randomly assigned to control and nature interventions using 2-D video played for 15 minutes three times a week for three weeks. Nature connectedness, perceived restorativeness and psycho-physiological well-being were measured. Significant changes were recorded in psychological stress levels after interventions compared with the baseline, including increased happiness and stronger emotions of comfort and relaxation. Our preliminary findings show that when compared with the control group, the intervention group has significantly higher levels of nature connectedness, happiness, and positive affect. The study findings suggest that virtual nature contact can improve participants’ sense of connectedness to nature, promote happiness, and reduce psycho-physiological stress. Our preliminary findings highlight the role of virtual nature contact in bolstering university students’ mental well-being at times of pandemic or when in-person visit to the natural environment is not feasible.